1945
DOI: 10.6028/jres.034.003
|View full text |Cite
|
Sign up to set email alerts
|

Spectrographic determination of sodium, potassium, and lithium in portland cement with the direct-current carbon arc

Abstract: Spectrographic methods, which are much less time-consuming than the usual chemical m ethods, are described for the determination of sodium, potassium, and lithium in portland cement. For the determination of sodium and potassium the sample is mixed with a mineral base containing silver for the internal standard. For lithium a standard mixture of graphite and strontium carbonate is added to the cement sample. In either case a fixed amount of the resultant mixture is placed in the crater of a graphi te electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1948
1948
1954
1954

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…An alternating current spark method of analy-zing the samples was chosen, not because it was the only procedure that would work but because the author had had experience with such methods and was able to predict results somewhat better than by other procedures. Burdett and Jones have obtained good results using a multisource power unit (1) and Helz has obtained satisfactory results using a direct current arc source (6).…”
Section: Quantitative Methodsmentioning
confidence: 99%
“…An alternating current spark method of analy-zing the samples was chosen, not because it was the only procedure that would work but because the author had had experience with such methods and was able to predict results somewhat better than by other procedures. Burdett and Jones have obtained good results using a multisource power unit (1) and Helz has obtained satisfactory results using a direct current arc source (6).…”
Section: Quantitative Methodsmentioning
confidence: 99%
“…Effect of One Alkali on Determination of the Other. In determining sodium in Portland cement, Helz (7) found that the potassium concentration had a marked effect on the sodium-cobalt ratio. Workers in flame photometry have also observed the effect of potassium on sodium-lithium ratios (1).…”
mentioning
confidence: 99%
“…analyzed by exciting the sample in the form of conducting briquets prepared from mixtures of the sample with special flake graphite (8). The practical availability of adequate quantities of sample to prepare briquets routinely for excitation appeared to exclude this technique as applied to the analysis of minute quantities of ash matter, however.…”
mentioning
confidence: 99%
“…The practical availability of adequate quantities of sample to prepare briquets routinely for excitation appeared to exclude this technique as applied to the analysis of minute quantities of ash matter, however. Alkaline salts are among substances commonly used as buffers in spectrochemical analysis (3,5,7,8,19). Some investigators have used lithium carbonate as a common matrix substance for the analysis of inorganic substances.…”
mentioning
confidence: 99%